PERAN GURU BIMBINGAN DAN KONSELING DALAM MENINGKATKAN KECERDASAN EMOSIONAL PESERTA DIDIK MTS MA’HAD AL-ZAYTUN - Eti, Eti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The rise of bullying is often attributed to social factors; however, it may also indicate a lack of emotional intelligence in the perpetrators. This study adopts a qualitative approach using field research. The objective of the study is to explore and describe the role of guidance and counseling teachers in enhancing students’ emotional intelligence at MTs Ma’had Al Zaytun, the strategies employed by these teachers, and the factors that influence their efforts in this regard. The findings reveal that guidance and counseling teachers play an active role in developing students’ emotional intelligence at MTs Ma’had Al Zaytun. Strategies implemented include a firm yet empathetic approach, individual counseling sessions, parental involvement, and training in social skills. Supporting factors in improving students’ emotional intelligence include family and school community support, the presence of effective bullying prevention and intervention programs, and a school environment conducive to emotional development. In contrast, inhibiting factors consist of a lack of awareness and understanding of the importance of emotional intelligence, limited resources, and high academic pressure.